Neuroglobin upregulation induced by 17β-estradiol sequesters cytocrome c in the mitochondria preventing H(2)O(2)-induced apoptosis of neuroblastoma cells - De Marinis, E (Nature Publishing Group, 2013)
The sex steroid hormone 17β-estradiol (E2) upregulates the levels of neuroglobin (NGB), a new neuroprotectant globin, to elicit its neuroprotective effect against H(2)O(2)-induced apoptosis. Several mechanisms could be proposed to justify the NGB involvement in E2 prevention of stress-induced apoptotic cell death. Here, we evaluate the ability of E2 to modulate the intracellular NGB localization and the NGB interaction with mitochondrial cytochrome c following the H(2)O(2)-induced toxicity. Present results demonstrate that NGB is expressed in the nuclei, mitochondria, and cytosol of human neuroblastoma SK-N-BE cells. E2, but not H(2)O(2) treatment of SK-N-BE cells, reallocates NGB mainly at the mitochondria and contemporarily reduces the number of apoptotic nuclei and the levels of cleaved caspase-3. Remarkably, the E2 treatment strongly increases NGB–cytochrome c association into mitochondria and reduces the levels of cytochrome c into the cytosol of SK-N-BE cells. Although both estrogen receptors (ERα and ERβ) are expressed in the nucleus, mitochondria, and cytosol of SK-N-BE cells, this E2 effect specifically requires the mitochondrial ERβ activity. As a whole, these data demonstrate that the interception of the intrinsic apoptotic pathway into mitochondria (i.e., the prevention of cytochrome c release) is one of the pivotal mechanisms underlying E2-dependent NGB neuroprotection against H(2)O(2) toxicity.